Open Archives initiative: A fast way of integration into global open science - Yurii Tkachov (Challenges and Issues of Modern Science)
Purpose: This article aims to analyze and summarize the practical experience of deploying and integrating platforms for open journals, conferences, and repositories with support for the Open Archives Initiative Protocol for Metadata Harvesting (OAI-PMH). It highlights the errors and challenges that journal and repository managers and administrators, as well as conference organizers, may encounter and offers recommendations to prevent and avoid these issues. Design / Method / Approach: The research is based on the analysis of real cases of deploying platforms for open science, including the analysis of errors and difficulties encountered during this process. The methodology includes the analysis of real-world cases, applying methods such as testing, validating the OAI-PMH protocol, observation, and studying regulatory and technical documents. Findings: Key errors and difficulties that organizers may face when creating open journals, conferences, and repositories with OAI-PMH support have been identified. Specific solutions are proposed to ensure the reliable operation of the metadata harvesting protocol (PMH), initial setup, and further integration of these platforms. Theoretical Implications: The study extends the understanding of the problems and challenges in the field of open science, particularly concerning the organizational and technical aspects of platforms with OAI-PMH support. Practical Implications: Practical recommendations are provided for administrators and managers of open journals, conferences, and repositories to avoid common mistakes and effectively use OAI-PMH to ensure data interoperability and accessibility. Originality / Value: The article presents an original analysis of real cases of implementing and integrating platforms with OAI-PMH support, making it a valuable resource for practitioners in the context of deploying platforms for open science. Research Limitations / Future Research: The study is limited to the analysis of specific cases and does not cover all possible aspects of deploying and integrating web applications with OAI-PMH support. Future research may focus on the quantitative analysis of the effectiveness of implementing these platforms and their long-term impact on open science. Paper Type: Case Study / Practitioner Paper.